2018
DOI: 10.3390/antiox7120179
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Cystinosin in the Intermediary Thiol Metabolism and Redox Homeostasis in Kidney Proximal Tubular Cells

Abstract: Cystinosin is a lysosomal transmembrane protein which facilitates transport of the disulphide amino acid cystine (CySS) from the lysosomes of the cell. This protein is encoded by the CTNS gene which is defective in the lysosomal storage disorder, cystinosis. Because of the apparent involvement of cystinosin in the intermediary thiol metabolism, its discovery has fuelled investigations into its role in modulating cellular redox homeostasis. The kidney proximal tubular cells (PTCs) have become the focus of vario… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 71 publications
0
14
0
Order By: Relevance
“…Moreover, oxidized cysteine exists mainly extracellularly and comprises two dynamic pools, the free oxidized and the CysSSP. Both pools might represent a way to supply cysteine into the cell [ 7 , 16 , 38 , 44 ], so we also analyzed the ratio between them. We observed that longer periods of CIH favors increased free oxidized cysteine instead of CysSSP pool ( Figure 6 E).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, oxidized cysteine exists mainly extracellularly and comprises two dynamic pools, the free oxidized and the CysSSP. Both pools might represent a way to supply cysteine into the cell [ 7 , 16 , 38 , 44 ], so we also analyzed the ratio between them. We observed that longer periods of CIH favors increased free oxidized cysteine instead of CysSSP pool ( Figure 6 E).…”
Section: Resultsmentioning
confidence: 99%
“…GSH is a tripeptide of glutamate, cysteine, and glycine and is synthesized in a process involving two enzymatic reactions, each requiring one ATP molecule [18]. Studies suggest that cystinotic cells are more vulnerable to oxidative stress as a result of impaired GSH synthesis and a compromised gamma glutamyl cycle, possibly due to altered mitochondrial function and depleted ATP levels [7,[19][20][21][22]. Reduced levels of GSH result in the inability of the cell to scavenge ROS, which puts the cells under oxidative stress, particularly in the mitochondria where most cellular ROS are produced.…”
Section: Oxidative Stress Leading To Mitophagymentioning
confidence: 99%
“…(i) Vision—retinol dehydrogenases are crucial in creating retinal, a major component of the visual cycle in animals [ 42 ]. (ii) Digestion and detoxification—cystinosin homolog and glutathione S-transferases are both involved in digestion [ 43 , 44 ]. In particular glutathione S-transferase is a powerful antioxidant that has been linked to detoxification in other insects, including the model beetle, Tribolium castaneum , by increasing the solubility of toxins for easy removal [ 44 ].…”
Section: Resultsmentioning
confidence: 99%